โปรติโอมิกส์เชิงเปรียบเทียบของโปรตีนของรากข้าว Oryza sativa L. ภายใต้ภาวะแล้ง - นวมินทร์ สงวนหมู่ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Comparative root proteomics under drought stress of two rice lines with the similar genetics background, Leung Pratew123 (LPT123) rice and its mutated drought resistant line, LPT123-TC171 was performed. One month-old rice seedlings were treated with 10% polyethylene glycol (PEG6000) for 0, 2, 6, 24 hours. The proteomes were analyzed by using GeLC-MS/MS to display the different protein expression patterns when plants were grown in drought or non-drought condition. Among 597 proteins identified, 122 proteins of LPT123 or LPT123-TC171 rice show significant difference in protein expression under drought stress- and normal-grown conditions. With the analysis of variance to determine the significance of each protein quantity from LPT123 and LPT123-TC171 grown in normal or drought stress condition, 96 proteins were detected and they could be classified to be involved in metabolic pathway, signal transduction, transcriptional regulator and ribosomal proteins and translation, cytoskeleton synthesis, cellular transport. OsNFXL1 was selected for the investigation at the transcriptional level as its orthologs in Arabidopsis were previously shown as drought responsive genes and rice micro-array database demonstrated that it had salt and drought responsive characters. The quantitative reverse transcription-polymerase chain reaction for OsNFXL1 gene expression showed the consistency with protein profiles in both LPT123 and LPT123-TC171. The possible functions of OsNFXL1 gene expression in drought tolerance were discussed.